System and method for a logical-model based application understanding and transformation - Chandra, Satish; Field, John H; Komondoor, Raghavan; Ramalingam, G.; Sinha, Saurabh (2009)
Disclosed is a method of and a system for establishing a logical-model based understanding of a legacy application. The method comprises the steps of providing a physical data model of the legacy application, said physical data model having a plurality of physical elements; establishing a logical data model for the legacy application, said logical data model having a plurality of logical model elements; and establishing links between said logical model elements and said physical elements. One of said physical or logical elements is selected, and said links are used to identify all of the physical or logical elements that are linked to said selected one of said elements. The preferred system may include a component for browsing and navigating the physical data model, logical data model, or the links between them, a component to answer queries about the application expressed using the logical data model, and a component to create a relational data model to support the migration of data stored in legacy databases (including flat files) to relational databases.